Drug–Drug Interactions of Infectious Disease Treatments in Low‐Income Countries: A Neglected Topic?. Issue 6 (21st March 2019) - McFeely, Savannah J.; Yu, Jingjing; Zhao, Ping; Hershenson, Susan; Kern, Steven; Ragueneau‐Majlessi, Isabelle; Hartman, Dan
Abstract : Despite recent advances in recognizing and reducing the risk of drug–drug interactions (DDIs) in developed countries, there are still significant challenges in managing DDIs in low‐income countries (LICs) worldwide. In the treatment of major infectious diseases in these regions, multiple factors contribute to ineffective management of DDIs that lead to loss of efficacy or increased risk of adverse events to patients. Some of these difficulties, however, can be overcome. This review aims to evaluate the inherent complexities of DDI management in LICs from pharmacological standpoints and illustrate the unique barriers to effective management of DDIs, such as the challenges of co‐infection and treatment settings. A better understanding of comprehensive drug‐related properties, population‐specific attributes, such as physiological changes associated with infectious diseases, and the use of modeling and simulation techniques are discussed, as they can facilitate the implementation of optimal treatments for infectious diseases at the individual patient level.